Pengaruh Variabel Makro Ekonomi Terhadap Kinerja Reksa Dana Dengan Ihsg Sebagai Variabel Intervening - Pandu Prihanantyo, Andika; Akhmadi, Akhmadi; Purwanda, Eka (GEMA EKONOMI, 2023)
This study aims to determine whether the influence of macroeconomic variables proxied by bond yields and inflation on the performance of mutual funds with the composite stock price index (JCI) as an intervening variable. The population used in this study was all stock mutual fund products for the 2016-2021 period. The sample of this study amounted to 48 stock mutual fund products out of 389 total population with a sample of 72. The data analysis method used in this study is Path Analysis. By using the program SPSS 26.The results showed that macroeconomics using government bond yield proxies and inflation had a significant negative effect on mutual fund performance. Then, government bond yields and inflation have a significant positive effect on mutual fund performance. Then JCI cannot mediate the relationship between bond yields and mutual fund performance and the relationship between inflation and mutual fund performance.